2017
DOI: 10.21470/1678-9741-2017-0080
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism is a Risk Factor for Atrial Fibrillation after Coronary Artery Bypass Graft

Abstract: IntroductionFew reports in the world have shown a differential effect of hypothyroidism in relation to morbidity and mortality following cardiac surgery.ObjectiveTo determine the association between preoperative hypothyroidism, composite and disaggregated outcomes of mortality and complications in patients undergoing first-time isolated myocardial revascularization surgery.MethodsHistorical cohort of patients undergoing myocardial revascularization between January 2008 and December 2014, with 626 patients incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Our incidence of atrial brillation was approximate 20%, which was in agreement with previous reports [19,20]. Jaimes and his colleagues [21] reported that hypothyroidism was a risk factor for the onset of postoperative atrial brillation in patients undergoing CABG. But the exposed patients in their study included ones only with TSH elevation, and preoperative baseline characteristics were not evenly distributed among the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…Our incidence of atrial brillation was approximate 20%, which was in agreement with previous reports [19,20]. Jaimes and his colleagues [21] reported that hypothyroidism was a risk factor for the onset of postoperative atrial brillation in patients undergoing CABG. But the exposed patients in their study included ones only with TSH elevation, and preoperative baseline characteristics were not evenly distributed among the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…Our incidence of atrial fibrillation was approximate 20%, which was in agreement with previous reports [Kosmidou 2018;Zheng 2016]. Jaimes and his colleagues [Jaimes 2017] reported that hypothyroidism was a risk factor for the onset of postoperative atrial fibrillation in patients undergoing CABG. But the exposed patients in their study included ones only with TSH elevation, and preoperative baseline characteristics were not evenly distributed among the two groups.…”
Section: E874supporting
confidence: 92%
“…Worku et al 12 reported that both overt and SCH were associated with atrial fibrillation, but the sample size was small and only 52% of patients received a preoperative beta‐blocker. Jaimes et al 13 reported that hypothyroidism was a risk factor for the onset of postoperative atrial fibrillation while the preoperative baseline characteristics were not evenly distributed among the two groups.…”
Section: Discussionmentioning
confidence: 99%